Keputusan Jepang untuk mempertahankan Traktat kerjasama dan keamanan antara Amerika Serikat dan Jepang 1960 segabai respon atas kebangkitan Ekonomi Tiangkok. - Fardo Rahmandika (HI 14 UMY 170, 2014)
This undergraduate thesis examine the reason behind Japan’s decision to maintain The Treaty of Mutual Cooperation and Security Between The United States and Japan 1960. The treaty helped Japan to prevent external aggression in post Second World War and the spreading of Communism in Cold War. But since post Cold War the existence of the treaty has caused so many problems such as burden in Japan’s defence budget and the raping of local Okinawan women. Beside the treaty has lost its urgency following the dissolution of Soviet Union and the incapability of North Korea to be perceived as a threat. To explore the reason behind Japan’s decision to maintain The Treaty of Mutual Cooperation and Security Between The United States and Japan 1960, this undergraduate thesis uses Perfect Deterrence theory to analyze Japan’s foreign policy towards certain issues regarding People’s Republic of China because it is the only Communist state left in East Asia after the North Korea. This undergraduate thesis will show that the treaty has an objective to deter People’s Republic of China. Keywords: Japan, United States, China, deterrence